Contribution of Fiqh Maslahah Rules in the Formulation of Fatwa DSN MUI - Asmoi Asmoi; Ahmad Musadad (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This research is based on the need of Muslims for legal guidance that is responsive to the development of modern Islamic economics and finance. Fatwas have a strategic role in addressing contemporary issues, particularly in Indonesia through the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) as the authoritative institution in issuing fatwas. The purpose of this research is to analyze the role of the principle of maslahat as the main basis in the legal istinbath process carried out by DSN-MUI. The method used is a descriptive qualitative approach with a literature review of DSN-MUI fatwas as well as references to fiqh books and the principles of ushul fiqh. The results show that the principles of maslahat, such as ainama wujidati al-maslahatu fasamma hukmullahi, dar’u al-mafāsid muqaddam ‘alā jalb al-maṣāliḥ, and tasharruful imam ‘ala raiyatihi manutun bi al-maslahah, play an important role in adapting Sharia law to the dynamics of modern finance. In conclusion, the application of the principle of maslahat allows the DSN-MUI fatwa to remain contextual, flexible, and relevant without abandoning the basic principles of Islamic law.